Qualitative evaluation of a pilot educational intervention to increase primary care HIV-testing - Kesten, Joanna M.; Davies, Charlotte F.; Gompels, Mark; Crofts, Megan; Billing, Annette; May, Margaret T.; Horwood, Jeremy (BMC family practice, 2019)
Background UK guidelines recommend a ‘routine offer of HIV testing’ in primary care where HIV diagnosed prevalence exceeds 2 in 1000. However, current primary care HIV testing rates are low. Efforts to increase primary care HIV testing are needed. To examine how an educational intervention to increase HIV testing in general practice was experienced by healthcare professionals (HCPs) and to understand the perceived impacts on HIV testing. Method Qualitative interviews with general practitioners (GPs) and nurses 3-months after receiving an educational intervention developed from an adapted version of the Medical Foundation for HIV and Sexual Health (MEDFASH) HIV Testing In Practice (TIPs) online educational tool which included training on HIV associated clinical indicator conditions, why, who, and how to test. The intervention was delivered in 19 high-HIV prevalence general practices in Bristol. 27 semi-structured interviews were conducted across 13 practices with 16 GPs, 10 nurses and the sexual health clinician who delivered the intervention. Transcripts were analysed thematically informed by Normalisation Process Theory. Results HCPs welcomed the opportunity to update their HIV knowledge through a tailored, interactive session. Post-training, HCPs reported increased awareness of HIV indicator conditions, confidence to offer HIV tests and consideration of HIV tests. Continued testing barriers include perceived lack of opportunity. Conclusions This qualitative study found that HIV education is perceived as valuable in relation to perceived awareness, confidence, and consideration of HIV testing. However, repetition and support from other strategies are needed to encourage HCPs to offer HIV tests. Future interventions should consider using behaviour change theory to develop a complex intervention that addresses not only HCP capability to offer an HIV test, but also issues of opportunity and motivation.